Changes in WBC and platelet count in patients with malaria: a hospital based comparative study - Jojera, Amit S.; Hathila, Rasik N.; Patel, Prashant R.; Tailor, Hemali J. (International Journal of Research in Medical Sciences, 2017)
Introduction: Malaria is one of the most common infectious diseases of tropics. It presents with varied clinicopathological manifestations. Most of the complication in malaria occurs due to various hematological abnormalities. Present study was aimed to find out abnormalities in WBC and platelet counts in patients with malaria. Methods: A total 135 patients either hospitalized or treated on an outpatient basis were included in the study after positive identification for malarial parasites on Giemsa stained PSMP smears. WBC and platelet count was carried out on 3 part hematology analyzer (Sysmax KX 21). WBC count less than 4000/cumm was considered as leucopenia and platelet count less than 150000/cumm was considered as thrombocytopenia. Results: The present study includes 135 patients with malaria from which 72.59% of subjects were male and 27.41% of subjects were female. P. falciparum was present in 68.89% of cases, P. vivax in 28.15% of cases. Majority of patients had normal leucocyte count (97.03%). Neutrophilia with lymphopenia was observed in both species of malaria in our study. Thrombocytopenia was observed in89.62% of cases in malaria. Thrombocytopenia in P. falciparum was found in 92.48% of cases and in P. vivax it was 81.57% of cases. Conclusion: Present study did not show any significant change in WBC count. Present study showed neutrophilia with relative lymphopenia in both group of malaria. Incidence of thrombocytopenia was observed in both species of malaria without any statistical significance.